Analyzing the Financial Performance of PT. Steel Pipe Industry of Indonesia Tbk - Widjanarko, Bambang; Panjinata, Awan; Sukoco, Agus; Suyono, Joko (International Journal of Industrial Engineering, Technology & Operations Management, 2023)
The financial report is a vital tool for acquiring insights into a company's financial position and business performance. Through financial statement analysis, crucial indicators pertaining to the company's financial health are unveiled, rendering it a valuable resource for guiding financial decision-making processes and offering a comprehensive portrayal of the company's performance. This study evaluates the financial performance of PT Steel Pipe Industry of Indonesia Tbk. and forecasts the company's sales turnover over the next five years. This research adopts a quantitative descriptive approach, utilizing secondary data spanning from 2018 to 2022 from the PT Steel Pipe Industry of Indonesia Tbk. The data analysis process encompasses several stages, including (i) Ratio Analysis of Financial Reports from 2018 to 2022, (ii) Compilation of sales data, (iii) Projections of sales figures using the least squares method, and (iv) Forecasting profits for the period from 2023 to 2027. The findings of this study indicate that the PT Steel Pipe Industry of Indonesia Tbk. is facing challenges in its financial performance, as the ratio values consistently fall below industry-standard financial metrics. However, the company has demonstrated resilience in maintaining its profitability levels, evidenced by a 6% increase in profit percentage in 2021 compared to 2020. This can be attributed to the company's consistent profit generation efforts, resulting in year-on-year profit growth.